2010
DOI: 10.1007/s00221-010-2249-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for predictive control in lifting series of virtual objects

Abstract: The human motor control system gracefully behaves in a dynamic and time varying environment. Here, we explored the predictive capabilities of the motor system in a simple motor task of lifting a series of virtual objects. When a subject lifts an object, she/he uses an expectation of the weight of the object to generate a motor command. All models of motor learning employ learning algorithms that essentially expect the future to be similar to the previously experienced environment. In this study, we asked subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 26 publications
2
53
4
Order By: Relevance
“…Our main finding was that the motor prediction of force perturbations is based on averaging past experience (even after implicitly experiencing four consecutive trials of increasing force perturbations). In contrast to previous studies concentrating solely on horizontal reaching movements, here we also tested vertical reaching movements and found similar results, thereby refuting one possible explanation—that force expectation is based on movement's direction- for the discrepancy between adaptation to force perturbations during reaching movements and adaptation to weight in a lifting task, for which motor memory was demonstrated to predict the next object rather than the average (Mawase and Karniel, 2010). …”
Section: Discussionsupporting
confidence: 68%
“…Our main finding was that the motor prediction of force perturbations is based on averaging past experience (even after implicitly experiencing four consecutive trials of increasing force perturbations). In contrast to previous studies concentrating solely on horizontal reaching movements, here we also tested vertical reaching movements and found similar results, thereby refuting one possible explanation—that force expectation is based on movement's direction- for the discrepancy between adaptation to force perturbations during reaching movements and adaptation to weight in a lifting task, for which motor memory was demonstrated to predict the next object rather than the average (Mawase and Karniel, 2010). …”
Section: Discussionsupporting
confidence: 68%
“…Infants might rely on tactile information and perceive the weight of the object proprioceptively prior to lifting (during a period of enhanced grip force prior to lifting; Johansson and Flanagan 2009;Gordon et al 1991;Johansson and Westling 1988). Another option is that infants maintain a sensorimotor memory based on the preceding lift to make a fair assumption about the current weight (Buckingham and Goodale 2010b;Gordon et al 1993;Mawase and Karniel 2010). These options are not mutually exclusive, and more research is needed to investigate whether infants solely rely on one or a combination of the two.…”
Section: Discussionmentioning
confidence: 94%
“…To achieve this, multiple sources of information need to be integrated (Nowak et al 2013). We know that adults rely on visual information (Buckingham et al 2009;Buckingham and Goodale 2010a;Cole 2008;Gordon et al 1991), sensorimotor memory (Buckingham and Goodale 2010b;Gordon et al 1993;Mawase and Karniel 2010), and tactile information (Johansson and Flanagan 2009;Gordon et al 1991;Johansson and Westling 1988) to prospectively control their lifting actions. All these sources of information are available prior to liftoff.…”
Section: Introductionmentioning
confidence: 99%
“…This default strategy of applying equal load force on both objects would result in overshoots in case of the light object and in too low lifting amplitudes on case of the heavy object. If infants instead do not rely on vision, but on either tactile information 22 from the brief period between the first manual contact with the object and lift-off (as shown in adults, Johansson & Westling, 1984;Johansson & Flanagan, 2009) or on sensorimotor memories 23 from the preceding trial (as shown in adults, Buckingham & Goodale, 2010b;Mawase & Karniel, 2010), the lifting pattern as described in the non-visual hypothesis should occur (2b). There would be no difference between both conditions in lifting amplitude, as all infants would use the same non-visual information.…”
Section: Study I -Prospective Motor Control Of Current Actions (Lifting)mentioning
confidence: 99%